A case series study in new restorative surgery in thumb amputation: The Adiposofaciocutaneous flap technique for distal thumb amputation replantation - Parviz Ahangar; Mohsen Akbaribazm; Mohsen Rahimi; Hosein Pirmohamadi (Trauma Case Reports)
Thumb distal amputation refers to the loss of a portion of the thumb at or near the tip, which can be caused by various injuries such as crush injuries, lacerations, or avulsions. Several surgical methods can be used to repair thumb distal amputations, including composite graft, flap reconstruction, replantation, and amputation revision. In this case report, we describe a successful surgical procedure performed on three healthy men (19, 26, and 44 years old) who suffered a sharp amputation of their left and right hands thumb. In one case initial fixation of the amputated part was performed by a general orthopedic surgeon as a composite graft, two other cases were referred us without any procedure. The procedure involved irrigation and minimal debridement and deepithelializing the amputated part and fixation it with one or two 1.5 mm steinman pins and repairing the nail bed with7/0 absorbable sutures. An adiposofaciocutaneous flap from the index finger was used to cover the pulp of the thumb and the nail bed, while a full-thickness grafts from the same wrist in one case and medial part of ipsilateral arm in others were used to repair the defect on the dorsal side of the index finger. The wound was dressed, and the sutures were removed after two weeks. The base of the flap was detached from the index finger after three weeks, and the kwires were removed after six weeks. The flap and graft were successfully taken, except for a small part of the tip of the thumb. Two years after the operation, in two patients and 3 months in whom was operated recently, all the patient's thumbs had a reasonable shape and length with minimal nail deformity. The use of an index finger based adiposofaciocutaneous flap and full-thickness graft in these cases allowed for successful reconstruction of the thumb and, improving both function and appearance.